Islamic Reform and Intellectual Accountability: Insights from the Life of Jamal Al-Din Al-Qasimi - Khadeja Soude (Universitas Muhammadiyah Malang, 2024)
This article explored the life, ideas, and reforming methods of the renowned Syrian scholar Jamal Al-Din Al-Qasimi (1854–1914), whose substantial publications and thoughtful contributions had a profound impact on the Islamic world. During the 19th and early 20th centuries, when there was a great deal of intellectual and sociopolitical change, al-Qasimi was a prominent reformist thinker. He became a prominent voice in the fight against stagnation in Muslim society and for the revival of Islamic philosophy after being born in Damascus, Syria. As he tackled modern issues including the effects of colonialism, internal sectarianism, and intellectual decline, his scholarly pursuits were distinguished by an unshakeable dedication to maintaining the integrity of Islamic teachings. This work examines Al-Qasimi's influence on reformist philosophy using a historical analysis methodology, paying special attention to his social and intellectual activities. His involvement in important historical challenges, both literal and symbolic, that put his fortitude as a reformer to the test are highlighted in particular. The hallmark of his reformist legacy is his capacity to remain intellectually balanced in the face of divisive subjects. As to the findings, Al-Qasimi was a key player in tackling the issues of his time because of his thoughtful intellectual stance, support for an awakening of fundamental Islamic values, and stress on reason and critical thinking. Islamic philosophy is still influenced by his legacy in discussions about intellectual responsibility and reform. The extending significance of his approaches in managing the challenges of modernity is highlighted by this study.